Analisis Kebutuhan Modal Kerja Padatoko Bangunan Sukarame Di Tenggarong - Sabran, Sabran (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2017)
This research was to analyze the Working Capital Needs Analysis On two Building Stores, The object of this research are Stores Building Excitement on AM. Sangaji Street Rt.7 Number 34 and Building Stores Sukarame on Sukarame Streetnumber 142 Tenggarong. In Stores Building Excitement has 3 employees and Stores Building Sukarame has four employees, the two stores have opening hours are usually from 08:00 - 20:00 at night. Capital resources of both stores are from their own capital and they have no debts.The purpose of this study was to determine the amount of working capital needs in Stores Building Sukarame In Tenggarong and to answer the truth of the hypothesis that the researchers propose.In general the method used to calculate the amount of working capital needed is to first determine the amount of working capital requirements and the large amount of cash required minimum. Working capital needs can be determined by calculating the various product units sold minus the costs incurred. The result of this research that working capital need on Building Store Sukarame in 2016 higher than in the working capital need in 2015. Keywords: Working Capital Needs